(untitled) (Fiep Bulletin - online, 2013)
The supervised internship is one of the first moments of closeness with the academic workplace. It is from this moment that the scholar could identify the specifics of a place, a community or a school and has a great importance during training. This article’s main objective is to describe / analyze the pedagogical practice of a teacher educator working in physical education in elementary education from 1st to 4th year of supervised internship during the systematic observation. The method of descriptive procedure was used. The target audience a teacher’s headcount school and monitoring of physical education classes, took from a group of 4th year, in the afternoon, and in total 25 students / as, 13 boys and 12 girls, besides using instruments such as; observation, field notes, structured interview with the teacher. For greater methodological rigor of the interviews we chose to discourse analysis. As the result of research the professor said it prefers to remain in the classroom to stand in coordinating education, their classes are geared to recreation, it claimed to have a good loving relationship with the students, plus there is a high incidence of children running by school boys playing football during recreation, girls playing hopscotch, jump on elastic, but without proper guidance that the / a teacher / a Physical Education knows pass on to their students / as. The other dance was content to be applied during PE lessons the teacher, however, was only intended for building choreography for the presentation of children in the event of final year of school. Therefore, it was observed that the teacher has some difficulty as any teacher, however we are trying to teach physical education classes without having initial training.